Dynamic analysis of railway vehicle-track interactions due to wheel flat with a pitch-plane vehicle model - Uzzal, Rajib Ul Alam; Ahmed, Waiz; Rakheja, Subhash (Journal of Mechanical Engineering, 2009)
<!--[if gte mso 9]> Normal 0 false false false MicrosoftInternetExplorer4 <![endif]--><!--[if gte mso 9]> <![endif]--> <!--[if gte mso 10]> <![endif]--> This paper presents the responses of the railway vehicle and track components in terms of contact forces and displacements. The considered vehicle model is a five-DOF pitch-plane lumped parameter quarter car model supported on two-dimensional track systems comprising three layers. The car body is linked with the vehicle bogie through secondary suspension springs and damper elements, which is further linked to the wheels through primary suspension springs and damper elements. In modeling of the track, the rail is considered as an infinitely long beam discretely supported by a series of springs, dampers and masses representing the elasticity and damping effects of the rail pads, ballasts, and subgrades respectively. The non-linear Hertzian contact theory is employed to accomplish the dynamic interactions between the lumped mass vehicle and the continuous rail. The drastic effect of one wheel flat to the other perfect wheel-rail contact point is also taken into account. Keywords: Wheel flat, pitch-plane vehicle, wheel-rail impact, component force. doi:10.3329/jme.v39i2.1851 Journal of Mechanical Engineering, Vol. ME39, No. 2, Dec. 2008 86-94